2021
DOI: 10.1038/s42004-020-00444-4
|View full text |Cite
|
Sign up to set email alerts
|

Single hydrogen atom manipulation for reversible deprotonation of water on a rutile TiO2 (110) surface

Abstract: The discovery of hydrogen atoms on the TiO2 surface is crucial for many practical applications, including photocatalytic water splitting. Electronically activating interfacial hydrogen atoms on the TiO2 surface is a common way to control their reactivity. Modulating the potential landscape is another way, but dedicated studies for such an activation are limited. Here we show the single hydrogen atom manipulation, and on-surface facilitated water deprotonation process on a rutile TiO2 (110) surface using low te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…The positively charged state of OH br on the rutile surface has been well identified by the imaging mechanism of AFM , and the direct measurement of the local surface potential of OH br by Kelvin probe force microscopy (KPFM), which successfully revealed the charging behavior on the atomic and nanometer scales. An electron from OH br transferring to TiO 2 forms an in-gap state, which is known as a polaronic state. On the other hand, although the density functional theory (DFT) calculation results suggested that OH t on the rutile surface is a negatively charged species, , there is no direct observation of the charged states of OH t . In addition, there are many studies about coadsorbed OH t neighboring H 2 O, OH br , and oxygen adatoms (O ad ), but the adsorption structure of isolated OH t has been under discussion, e.g., whether isolated OH t forms a H bond with the TiO 2 surface. ,, The hydroxyl-induced charge state of adsorbed organic molecules on the TiO 2 surface is reported …”
Section: Introductionmentioning
confidence: 99%
“…The positively charged state of OH br on the rutile surface has been well identified by the imaging mechanism of AFM , and the direct measurement of the local surface potential of OH br by Kelvin probe force microscopy (KPFM), which successfully revealed the charging behavior on the atomic and nanometer scales. An electron from OH br transferring to TiO 2 forms an in-gap state, which is known as a polaronic state. On the other hand, although the density functional theory (DFT) calculation results suggested that OH t on the rutile surface is a negatively charged species, , there is no direct observation of the charged states of OH t . In addition, there are many studies about coadsorbed OH t neighboring H 2 O, OH br , and oxygen adatoms (O ad ), but the adsorption structure of isolated OH t has been under discussion, e.g., whether isolated OH t forms a H bond with the TiO 2 surface. ,, The hydroxyl-induced charge state of adsorbed organic molecules on the TiO 2 surface is reported …”
Section: Introductionmentioning
confidence: 99%
“…All AFM experiments were performed on a home-built low-temperature ultrahigh vacuum AFM system. Following procedures previously described in (21)(22)(23)(24)(32)(33)(34), a Nanonis OC4 system with electronics and software was used for control and data acquisition. The optical beam deflection method was used to measure the deflection of the cantilever.…”
Section: Methodsmentioning
confidence: 99%